Analysis of the Frequency of Academic Staff and Students` Use of Information and Communication Technology (ICT) - Mbaba, A.E.; Shema, I.M. (Richtmann Publishing, 2012)
The paper analyze the frequency of academic staff and students use of information and communicationtechnology Ict in Katsina State College of Education, it explore the ability of staff and students incomputer application 114academic staff and 1995 students were engaged in the study. A survey researchdesign was used; the data collected was analyzed using percentage to present the responses. 4 point Likertscalewas used, while a mean of 2.50 was adopted to determine the higher and lower participation in theuse of ICT and ability in computer application. The finding show that the use of ICT in the College is high[m=2.78 higher than m=2.50]. The study also indicated that the academic staff are more competent in theuse of wide range of computer applications than students [m=3.08and 2.56 respectively] the study revealsthat the staff and students actually engaged in the use of ICT almost on a daily basis for both schoollearning and individual use. The researchers therefore recommend that this study should be carried out inall the tertiary institutions in Nigeria to clarify the uncertainty of the frequency of ICT use in Nigeriaschools.